129 Intra-abdominal Compartment syndromecomplicating postoperative gastroschisis neonate – a learning lesson. (11th October 2021) - Kaninde, Abhidhamma; Battiwala, A; Taha, S; Mittal, S
Abstract : Introduction: Abdominal compartment syndrome (ACS) is a known complication of abdominal wall defect repair which needs vigilant monitoring. Here we emphasise bladder pressure monitoring system as one of the tools for early detection of ACS. Case Summary: This was a term baby with an antenatal diagnosis of gastroschisis born by elective caesarean section. The baby was born in good condition and the abdominal contents were covered with a plastic bag to prevent fluid and heat loss, and a nasogastric tube was passed. The baby was taken to theatre within a few hours of birth for surgical repair. Intraoperative findings included the stomach, small and large bowel being outside of the abdominal cavity. In view of the repair being under moderate tension, bladder pressure monitoring for ACS was instituted using an indwelling catheter and standard pressure transducer. Over the following 12 hours, the bladder pressure gradually increased from a baseline of 8-10 mmHg to 24 mmHg. This was accompanied by oliguria, elevated lactate, a wide toe-core temperature gap and high ventilator pressure requirement to achieve the target tidal volume. Interestingly, the abdomen remained non-tender for a significant time period, which delayed early suspicion of ACS. But with worsening metabolic acidosis and increasing bladder pressure reading decision was made to take baby to theatre for laparotomy. Following decompressive laparotomy, the baby's clinical condition improved and observation parameters stabilised. Discussion: Gastroscisis is defined as a defect in the abdominal wall resulting in evisceration of abdominal contents. Its incidence is reported as around 1.35 per 10, 000 total birth in England and Wales as per Tan et. Risk factors include young maternal age and maternal cigarette smoking, alongside certain medications and maternal genitourinary infections. ACS can occur as a rare complication of surgical repair of gastroschisis, and can result in intestinal and renal ischaemia. As per Akhobadze et al sustained intra-abdominal pressure (IAP) of greater than 20 mm of Hg is defined as abdominal compartment syndrome. Intravesical pressure monitoring is recommended by the World Society for Abdominal Compartment Syndrome (WSACS) as the most reliable technique for IAP measurement. Clinical staff working in surgical neonatal unit should be aware of sensitivity of Intrabdominal pressure monitoring system over clinical signs of ACS. Conclusion: Abdominal signs may not appear in early abdominal compartment syndrome. Intraabdominal pressure monitoring is important for early diagnosis of abdominal compartment syndrome.